A Survey on Harmonic Mitigation Techniques in Power System - Abirami, P.; C.N.Ravi, Dr. (International Journal of Engineering and Technology, 2018)
In recent years, one of the most frightening criteria in power system is the generation of harmonics, due to the advancement in power semiconductor devices. Today most of the commercial, residential and industrial loads include advanced semiconductor technology and the utility of these non-linear loads results in harmonics generation on consumer’s premises. These harmonics plays a vital role in polluting the power quality of a distribution network by introducing losses which results in the failure of distribution side electrical equipment like transformer, protection, measuring devices, distribution feeders and so on. Hence to enhance the power quality, harmonic mitigation technique should be implemented in a distribution network. This paper surveys about the availability of various harmonic mitigation techniques with the analysis of its merits and demerits.